Women's views on screening for Type 2 diabetes after gestational diabetes: a systematic review, qualitative synthesis and recommendations for increasing uptake. Issue 1 (22nd July 2019) - Dennison, R. A.; Fox, R. A.; Ward, R. J.; Griffin, S. J.; Usher‐Smith, J. A.
Abstract: Aim: Many women do not attend recommended glucose testing following a pregnancy affected by gestational diabetes (GDM). We aimed to synthesize the literature regarding the views and experiences of women with a history of GDM on postpartum glucose testing, focusing on barriers and facilitators to attendance. Methods: We systematically identified qualitative studies that examine women's experiences following GDM relating to glucose testing (diabetes screening) or experience of interventions to promote uptake of testing. We conducted a thematic synthesis to develop descriptive and then analytical themes, then developed recommendations to increase uptake based on the findings. We evaluated the quality of each study and the confidence that we had in the recommendations using published checklists. Results: We included 16 articles after screening 23 160 citations and 129 full texts. We identified four themes of influences relating to the healthcare system and personal factors that affected both ability and motivation to attend: relationship with health care, logistics of appointments and tests, family‐related practicalities and concern about diabetes. We developed 10 recommendations addressing diabetes risk information and education, and changes to healthcare systems to promote increased attendance at screening in this population, most with high or moderate confidence. Conclusions: We have identified a need to improve women's understanding about Type 2 diabetes and GDM, and to adjust healthcare provision during and after pregnancy to decrease barriers and increase motivation for testing. Encouraging higher uptake by incorporating these recommendations into practice will enable earlier management of diabetes and improve long‐term outcomes. What's new?: There is a need to increase the number of women attending glucose testing after gestational diabetes. Higher attendance will enable earlier diagnosis and management of diabetes and improve long‐term outcomes. This is the first qualitative review focusing on barriers and facilitators to screening attendance. We found that factors could affect either mothers' motivation or opportunity to attend. Some influences related to the healthcare system (relationship with health care and logistics of the appointment and test), whereas others were personal (concern about diabetes and family‐related practicalities). We developed 10 recommendations to increase screening attendance based on the barriers and facilitators identified.